Overview of Elementary School Students' Career Awareness in Bandung City - Irmayanti, Rima; Suherman, Uman; Nurihsan, Juntika; Budiman, Nandang (PrimaryEdu : Journal of Primary Education, 2025)
Career awareness is defined as an individual's understanding of the roles and career paths they can choose, as well as the relationship between personal abilities and preferences with the demands of the workplace. Career awareness is a career development that needs to be achieved by students and needs to be given at the beginning of the school year, namely at the elementary school level. This article aims to describe the level of career awareness in elementary school students in the upper grades, namely starting from grades IV, V, and VI in the form of a general description of the level of achievement obtained by students at each level. This study uses a quantitative approach with a descriptive method. The number of research samples was carried out using random sampling techniques using Slovin calculations. Data collection was carried out by distributing questionnaires to 189 students in Bandung City. The results showed that most students in grades IV, V, and VI were in the high category. These results indicate that students in the upper grades have career awareness in accordance with the developmental stages that elementary school students should have. This achievement can support students in carrying out career development tasks at the next stage. Efforts that can be made to help develop students' career awareness, especially in schools, include introducing them to various jobs, exploring interests and talents, developing social skills, and using media and direct experience in career teaching.